Synthesis, structure and antiproliferative activity of chiral polyamines based on a 2-azanorbornane skeleton. Issue 16 (1st September 2016) - Kamińska, Karolina; Wojaczyńska, Elżbieta; Wietrzyk, Joanna; Turlej, Eliza; Błażejczyk, Agnieszka; Wieczorek, Robert
Graphical abstract: Abstract: A series of enantiopure 2-azanorbornane-based amines were prepared via a stereoselective aza-Diels–Alder reaction and further modifications of the obtained cycloadduct. In particular, derivatives containing two bicyclic moieties linked by NCCN fragments were synthesized. Two dimeric derivatives exhibited a significant antiproliferative activity against selected cell lines, comparable to cisplatin in certain cases. Abstract : N, N ′-Bis[(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl]methylethan-1, 2-diamine: C32 H46 N4 [ α ]D 20 = +41.1 ( c 0.32, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: bis (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : ( E )-1, 1-Diphenyl- N -[(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl]methylenemethanamine: C28 H30 N2 [ α ]D 20 = −24.9 ( c 0.42, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : ( E )-(1 S, 3 R, 4 R )-2-[( S )-1-Phenylethyl]-2-azabicyclo[2.2.1]heptan-3-al oxime: C15 H20 N2 O [ α ]D 20 = +16.9 ( c 0.26, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : (1 S, 3 R, 4 R )-2-[( S )-1-Phenylethyl]-3-aminemethyl-2-azabicyclo[2.2.1]heptane: C15 H22 N2 [ α ]D 20 = −26.1 ( c 0.23, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : N- Benzyl-bis-[(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl]methylamine: C37 H47 N3 [ α ]D 20 = +65.8 ( c 0.38, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: bis (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : N -1, 1, 1-Triphenylmethyl-bis-[(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl]methylamine: C49 H55 N3 [ α ]D 20 = +57.2 ( c 0.6, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: bis (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : N -Benzoyl-bis-[(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl]methylamine: C37 H45 N3 [ α ]D 20 = +69.6 ( c 0.66, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: bis (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation) Abstract : Bis-[(1 S, 3 R, 4 R )-2-(( S )-1-phenylethyl)-2-azabicyclo[2.2.1]heptan-3-yl]methylamine: C30 H41 N3 [ α ]D 20 = −13.9 ( c 0.5, CH2 Cl2 ) Source of chirality: chiral substrate Absolute configuration: bis (1 S, 3 R, 4 R, 1′ S ) (by chemical correlation)